A national propensity score-matched analysis of emergency laparoscopic versus open abdominal surgery. Issue 8 (16th March 2021) - Pucher, P H; Mackenzie, H; Tucker, V; Mercer, S J
Abstract: Background: Laparoscopy has been widely adopted in elective abdominal surgery but is still sparsely used in emergency settings. The study investigated the effect of laparoscopic emergency surgery using a population database. Methods: Data for all patients from December 2013 to November 2018 were retrieved from the NELA national database of emergency laparotomy for England and Wales. Laparoscopically attempted cases were matched 2 : 1 with open cases for propensity score derived from a logistic regression model for surgical approach; included co-variates were age, gender, predicted mortality risk, and diagnostic, procedural and surgeon variables. Groups were compared for mortality. Secondary endpoints were blood loss and duration of hospital stay. Results: Of 116 920 patients considered, 17 040 underwent laparoscopic surgery. The most common procedures were colectomy, adhesiolysis, washout and perforated ulcer repair. Of these, 11 753 were matched exactly to 23 506 patients who had open surgery. Laparoscopically attempted surgery was associated with lower mortality (6.0 versus 9.1 per cent, P < 0.001), blood loss (less than 100 ml, 64.4 versus 52.0 per cent, P < 0.001), and duration of hospital stay (median 8 (i.q.r. 5–14) versus 10 (7–18) days, P < 0.001). Similar trends were seen when comparing only successful laparoscopic cases with open surgery, and also when comparing cases converted to open surgery with open surgery. Conclusion: In appropriately selected patients, laparoscopy is associated with superior outcomes compared with open emergency surgery. Lay summary: Minimally invasive (laparoscopic) surgery has been widely adopted in elective surgery but is sparsely used in emergencies. The study used national data to look at outcomes for patients having laparoscopic or open surgery, and used statistical methods to match patients in each group for critical variables such as type of operation, age and how unwell they were at time of surgery. Laparoscopy was found significantly to improve outcomes with reduced duration of stay in hospital, and lower rates of death after surgery. This suggests laparoscopy should be considered for much wider use than is currently employed. Abstract : Laparoscopy has positively impacted elective surgical outcomes but is sparsely used in emergency major surgery. This population-level analysis suggests laparoscopy may reduce mortality and length of stay compared to propensity score-matched laparotomy. Greater adoption of minimally invasive emergency surgery may improve patient care.